2020
DOI: 10.1111/pce.13880
|View full text |Cite
|
Sign up to set email alerts
|

Innovative transcriptome‐based genotyping highlights environmentally responsive genes for phenology, growth and yield in a non‐model grain legume

Abstract: The narrow-leafed lupin, Lupinus angustifolius L., is a grain legume crop, cultivated both as a green manure and as a source of protein for animal feed and human food production. During its domestication process, numerous agronomic traits were improved, however, only two trait-related genes were identified hitherto, both by linkage mapping. Genome-wide association studies (GWAS), exploiting genomic sequencing, did not select any novel candidate gene. In the present study, an innovative method of 3 0-end reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 103 publications
(215 reference statements)
0
8
0
Order By: Relevance
“…Similarly, genetic maps developed in yellow lupin and quantitative trait locus (QTL) analysis for flowering time and anthracnose resistance have identified candidate genes for these traits (Iqbal et al, 2019; Lichtin et al, 2020). More recently, massive analysis of cDNA ends (MACE) was employed for 126 NLL lines surveyed in the field for several agronomic traits to conduct a genome wide association study (GWAS) to identify genes associated with these traits (Plewinski et al, 2020). Strong marker trait associations were identified for the start and end to flowering, maturity, plant height, yield and total grain weight, where the deletion in the major flowering time locus LanFtc1 (Taylor et al, 2019) was strongly associated with both the start and end to flowering as well as maturity (Plewinski et al, 2020).…”
Section: Overview Of Lupin Transcriptome Resources and Their Use In Prebreeding/breeding Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, genetic maps developed in yellow lupin and quantitative trait locus (QTL) analysis for flowering time and anthracnose resistance have identified candidate genes for these traits (Iqbal et al, 2019; Lichtin et al, 2020). More recently, massive analysis of cDNA ends (MACE) was employed for 126 NLL lines surveyed in the field for several agronomic traits to conduct a genome wide association study (GWAS) to identify genes associated with these traits (Plewinski et al, 2020). Strong marker trait associations were identified for the start and end to flowering, maturity, plant height, yield and total grain weight, where the deletion in the major flowering time locus LanFtc1 (Taylor et al, 2019) was strongly associated with both the start and end to flowering as well as maturity (Plewinski et al, 2020).…”
Section: Overview Of Lupin Transcriptome Resources and Their Use In Prebreeding/breeding Activitiesmentioning
confidence: 99%
“…More recently, massive analysis of cDNA ends (MACE) was employed for 126 NLL lines surveyed in the field for several agronomic traits to conduct a genome wide association study (GWAS) to identify genes associated with these traits (Plewinski et al, 2020). Strong marker trait associations were identified for the start and end to flowering, maturity, plant height, yield and total grain weight, where the deletion in the major flowering time locus LanFtc1 (Taylor et al, 2019) was strongly associated with both the start and end to flowering as well as maturity (Plewinski et al, 2020). The MACE technique was also used for expression QTL mapping in NLL, constituting the first e‐QTL survey in lupins (Plewinski et al, 2019).…”
Section: Overview Of Lupin Transcriptome Resources and Their Use In Prebreeding/breeding Activitiesmentioning
confidence: 99%
“…A valid alternative analysis was genome-wide association mapping (GWAS), which can be used to score the association between thousands of SNP markers and the desired t r a i t . T h u s , G W A S w a s r e c e n t l y e x p l o i t e d i n L. angustifolius, highlighting novel candidate genes for phenology, growth, and yield traits (Plewiński et al 2020). However, it was shown that GWAS can lead to false associations if the trait of interest is present in a very small proportion (< 5%) of the population (Sonah et al 2015).…”
Section: Genomic Selection Can Assist Marker-assisted Selection Of Anmentioning
confidence: 99%
“…Due to the unprecedented advances in NGS technology, an increasing repertoire of HTP markers in several underutilized legumes have helped to identify loci associated with aspects of complex trait architecture. GWAS has been assisted by the subsequent availability of genome-wide SNP markers for various traits, including phenological traits, quality/nutritional traits, biotic and abiotic stresses, and yield and yield-related traits, in many underutilized legumes ( Plewiński et al, 2020 ). In narrow-leafed lupin, a GWAS incorporating massive analysis of cDNA ends (MACE) markers in 126 gentoypes uncovered significant MTAs related to flower initiation, maturity, plant height, and yield traits ( Plewiński et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS has been assisted by the subsequent availability of genome-wide SNP markers for various traits, including phenological traits, quality/nutritional traits, biotic and abiotic stresses, and yield and yield-related traits, in many underutilized legumes ( Plewiński et al, 2020 ). In narrow-leafed lupin, a GWAS incorporating massive analysis of cDNA ends (MACE) markers in 126 gentoypes uncovered significant MTAs related to flower initiation, maturity, plant height, and yield traits ( Plewiński et al, 2020 ). The underlying candidate genes were Lup019134, Lup015264, Lup021911, and Lup021909 for flower initiation, Lup015264 and Lup004734 for maturity, Medtr1g030750 for plant height, and Lup021835 and Lup022535 for yield traits ( Plewiński et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%